Forest Food of the Tribal Population of Andaman and Nicobar Islands - Sangal, P. M. (Indian Forester, 1971)
Forest are an important source of food particularly for the tribal population (forest dwellers) which depends substantially on the edible products of the forests. A study of the food habits of the forest dwelling tribals is important not only for a better understanding of their needs in relation to management of forests but also for identifying potential sources of edible products which could be utilised in the wake of an emergency or cultivated as a source of food material or for industrial uses for the ever increasing needs of the general population. Forest food of the aborigines of Andaman and Nicobar Islands has been described.